Early Cretaceous mafic-intermediate dykes in the Dabie orogen as indicators for post-collisional lithosphere removal - Li, Shuang-Qing; Schmitt, Axel Karl; Chen, Fukun (Lithos, 2021)
The lithospheric root underneath the Dabie orogen, which is the key part of the Central Orogen of China, experienced a cycle of thickening during Triassic continent-continent collision with subsequent post-collisional collapse during the Early Cretaceous. However, the process and mechanism of how thickened lithospheric roots are removed generally remain controversial. U-Pb ages and oxygen isotopes of zircons along with whole-rock geochemistry of post-collisional mafic-intermediate dykes in the region were used to track magmatic contributions from the lower crust, and constrain magma provenance from compositionally variable reservoirs in the upper mantle. Relict zircons show evidence of recycling of subducted continental crust of South China Block that not only has the Neoproterozoic ages and experienced the Triassic metamorphism, but also contains both 18O-depleted and enriched components. A first generation of hypersthene-normative tholeiitic dykes and nepheline-normative alkaline dykes were emplaced at ca. 130-120 Ma. They are overall characterized by arc-like geochemical patterns with εNd values from −21.6 to −4.6 and initial 87Sr/86Sr from 0.7056 to 0.7094. Coeval alkaline dykes are shifted towards more depleted-mantle like compositions, indicating simultaneous melt extraction from different mantle domains and depths. In contrast, second-generation hypersthene-normative mafic dykes (ca. 115-110 Ma) show OIB-like characteristics with εNd values from −1.5 to +4.8 and initial 87Sr/86Sr ratios from 0.7039 to 0.7049, indicating an increasing contribution from upwelling asthenospheric mantle during lithospheric thinning. The temporal evolution of the geochemical characteristics of mafic melts derived from the upper mantle in the Dabie orogen is consistent with foundering of thickened lithosphere and subsequent influx of asthenospheric mantle. The removal of thickened lithosphere root is suggested to be triggered by subduction of the Paleo-Pacific plate and lasted from ca. 130-115 Ma as constrained by the intrusive ages of two distinct types of tholeiitic dykes.